THE IMPLEMENTATION OF DISCUSSION TECHNIQUE IN TEACHING SPEAKING - Agus Furyanto, Faoyan (Vidya Karya Jurnal Kependidikan, 2015)
This study were purposed to know the procedures of discussion technique and to find out the strengths and weaknesses of discussion technique when it was used to teach speaking. The research was a descriptive qualitative research. The subject of the research was the eighth grade students of MTSM 3 Al-Furqon Banjarmasin. The data were taken from observation, field notes and the interview. Further, the data were analyzed qualitatively. It was found that the implementation of discussion technique in teaching speaking was suitable with the procedures of discussion technique based on the theories. There were five stages that were implemented during teaching speaking using this technique and those procedures covered learning activities and studentsâ tasks to develope studentsâ pronunciation, grammar, vocabulary, fluency, and expression. The implementation of this technique gave strenghts and weaknesses. The strenghts were: 1) discussion technique could promote studentsâ speaking skil, 2) discussion technique could improve the class condition, and 3) discussion technique could improve the studentsâ participation in the speaking activities. While the weaknesess were: 1) some of students tended to be out of the tasks, and 2) teacher got difficulties to manage the time during discussion. In conclusion, the procedure of discusion techique was implemented properly and this technique gave more strenghts than weaknesess.